A crack-shear slip model of high-strength steel fiber-reinforced concrete based on a push-off test. (15th November 2016) - Jongvivatsakul, Pitcha; Attachaiyawuth, Anuwat; Pansuk, Withit
Highlights: Crack-shear slip model of high-strength steel fiber-reinforced concrete is proposed. Good agreement between the model and experimental results was observed. Direction of concrete flow and stirrups shows combined effect on shear strength. Abstract: This paper presents the shear behavior and a crack-shear slip model of high-strength steel fiber-reinforced concrete based on a push-off test. The parameters were the compressive strength of the concrete, steel fiber volume fraction, stirrup ratios, angle between the shear plane-flow direction in shear flow and angle between the shear plane-stirrups. The test results indicated that the shear strength increased by approximately 1.5–2 times due to the presence of steel fibers and the ductility effectively increased when using steel fibers and stirrups. The angle of the shear plane-flow direction in shear flow and the angle of the shear plane-stirrups significantly affected the shear strength. In this paper, a crack-shear slip model for high-strength steel fiber-reinforced concrete is proposed using the tri-linear relationship. The results calculated from the model corresponded with the test results.